Surface Modification of Pure Mg for Enhanced Biocompatibility and Controlled Biodegradation: A Study on Graphene Oxide (GO)/Strontium Apatite (SrAp) Biocomposite Coatings - Yigit, Oktay; Gurgenc, Turan; Dikici, Burak; Kaseem, Mosab; Boehlert, Carl; Arslan, Ersin (Mdpi, 2023)
Magnesium alloys have excellent biodegradability but suffer from high corrosion rates and unfavorable biological responses. Thus, a surface modification strategy to regulate the corrosion rate and enhance biocompatibility is required. In this study, pure Mg substrate surfaces were coated with strontium apatite (SrAp) and graphene oxide (GO) biocomposite structures using the hydrothermal method to increase the biocompatibility of the surface of the Mg and obtain a moderate biodegradation rate. The effect of the GO concentration (0, 2, 4, and 6 wt.%) on the surface microstructure and its corrosion behavior were systematically studied. The corrosion behavior of the coatings was characterized in-vitro using the electrochemical polarization method in Hank's solution. An EDS-connected SEM was used to examine the coatings' surface properties. The functional groups of the coatings were identified using ATR-IR spectroscopy. To determine the degree of crystallization and examine the elemental distribution of the coatings, an XRD was used with a grazing incidence attachment. The XRD and SEM-EDS results showed that increasing the GO ratio in the SrAp-based coatings significantly enhanced the homogeneity and crystallinity, and the ATR-IR spectroscopy revealed that the SrAp/GO coatings were rich in functional groups, including hydroxyl, phosphate, and carbonate groups, that are known to promote bone formation and regeneration. The results of the electrochemical polarization tests demonstrated a considerable decrease in the corrosion rates for the samples with SrAp matrix and GO coatings. Additionally, the coatings containing GO exhibited higher polarization resistance (Rp) values, indicating their potential as a promising surface modification technique for biodegradable implants. These findings suggest that incorporating GO into the SrAp coatings could enhance their biocompatibility and provide a moderate biodegradation rate, which is desirable for biomedical applications.
Keywords: pure Mg; surface modification; hydrothermal; graphene oxide (GO); strontium apatite (SrAp); in-vitro corrosion